1966
DOI: 10.1139/m66-154
|View full text |Cite
|
Sign up to set email alerts
|

An Electron Microscope Study of Thin Sections of Haemophilus Vaginalis (Gardner and Dukes) and Some Possibly Related Species

Abstract: The line structure of Haemophilus vaginalis (Gardner and Dukes 1955) was compared with that of four, possibly related species (Butyribacterium rettgeri, Corynebacterium diphtheriae var. mitis, Lactobacillus acidophilus, Haemophilus influenzae) and an unrelated species, Neisseria haemolysans, which had shown a similar degree of Gram-variability as that of H. vaginalis. Although H. vaginalis was first described as a Gram-negative rod, its fine structure, particularly that of cell wall and septa, was more like th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 8 publications
2
23
0
1
Order By: Relevance
“…Transmission electron microscopy of G. vaginalis has been reported (Reyn et al, 1966;Crisswell et al, 1972;Greenwood, 1983). Evidence of fibrillar material adhering to the cell wall has been found (Crisswell et al, 1972;Greenwood, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…Transmission electron microscopy of G. vaginalis has been reported (Reyn et al, 1966;Crisswell et al, 1972;Greenwood, 1983). Evidence of fibrillar material adhering to the cell wall has been found (Crisswell et al, 1972;Greenwood, 1983).…”
Section: Introductionmentioning
confidence: 98%
“…Reyn et al (188) provided the first ultrastructural evidence of the gram-positive character of G. vaginalis (Fig. 2) wall is relatively thin compared with the walls of reference strains of Corynebacterium diphtheriae, Butyribacterium rettgei, and Lactobacillus acidophilus.…”
Section: Introductionmentioning
confidence: 99%
“…A flocculent (82,188) or fibrillar (49) exterior layer was visualized by electron microscopy ( Fig. 2), and ruthenium red staining indicated that it has a polysaccharide component (80).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the organism is gram negative because of the presence of very little mucopeptide, the amino acid composition of the cell wall (2), and a "lipopolysaccharide-like" fraction (5); others suggest that it is gram positive on the basis of its pattern of septum formation (17), the absence of diaminopimelic acid (6), and its lipopolysaccharide (20). However, the results of the present susceptibility study are consistent with the notion that G. vaginalis is neither typically gram positive nor typically gram negative, since antimicrobial agents regarded as specifically active against gram-positive or gram-negative organisms showed relatively poor activity.…”
mentioning
confidence: 99%